A Note on the Painlevé Property of Coupled KdV Equations. (19th February 2014) - Sakovich, Sergei
Abstract : We prove that one system of coupled KdV equations, claimed by Hirota et al. to pass the Painlevé test for integrability, actually fails the test at the highest resonance of the generic branch and therefore must be nonintegrable.